The Identity Development Strategy for Business Rebranding according to Balance Creative Group Co.,Ltd.Model,Khon Kaen Province - นาชัยสินธุ์, ดวงจันทร์ (Journal of Fine and Applied Arts Khon Kaen University, 2018)
This article is a part of the Khon Kaen Real Estate Marketing Strategy for Rebranding Research Project. The objective of the study is to design and rebrand the corporate identity of the Balance Creative Group Company Limited in accordance with its business target in order to convey the corporate image. It reflects the distinct characteristics and forms; and results in the definition of the corporate rebranding onto its products and services to show that they are quality, creditable, and prominent. The concept of identity development strategy for business rebranding is about positioning and differentiation, and it is necessary for highlighting the characteristics of the brand which conform to Thailand 4.0 economic model where the economic and society are linked with digital technology and merged with participatory lifestyles of its consumers stably, prosperously, and sustainably. The author aims to present the concept of identity development strategy for business rebranding to clearly visualize the corporate identity in forms of media, symbols, colors, and slogans; which are unique to be used as guidelines for the development of products, services, buildings, and other kinds of things. The concept can be summarized and divided into three steps. The first step is ‘the study and data analysis for business rebranding’, this is to study the corporate’s information as a whole and to brainstorm the mutually agreed identity of the organization. The second one is ‘the design of the corporate identity symbol’ using the analyzed data as a guideline on the concept of the corporate’s specific communication platform. And the last one is ‘the definition of the corporate’s business identity’ made by concluding the specific form of the business rebranding and presenting the organization via the brand’s identity.